Níveis de substâncias tóxicas persistentes (PTS) em sangue de parturientes de sete áreas selecionadas do Estado de São Paulo - Brasil - Rudge, Cibele Vieira Cunha [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
OBJETIVO: Determinar substâncias tóxicas persistentes (PTS) no sangue de 160 parturientes em áreas do Estado de São Paulo-Brasil. SUJEITOS E MÉTODOS: Foram analisados os PCBs (99, 101, 118, 138, 153, 156, 163, 170, 180, 183, 187, 194) e pesticidas organoclorados ( -HCH, -HCH, -HCH, HCB, p,p'-DDE, p,p'-DDT, t-chlordane, cchlordane, oxy-chlordane, t-nonachlor and c-nonachlor) em sete áreas; duas rurais (Botucatu e Ribeirão Preto), uma industrial (Campinas), uma litorânea (Santos) e três urbanas em São Paulo (UNIFESP, Vila Nova Cachoeirinha e Leonor Mendes de Barros). Valores abaixo do limite de detecção (LOD) foram substituídos por 0.5XLOD. Teste de Kruskall Wallis e Dumm compararam as áreas com níveis de PTS acima do LOD. O projeto foi aprovado pelo CEP da FMB. RESULTADOS: Os valores das PTS (ng/g lipideo) foram baixos. PCBs 118, 138, 153, p-p’-DDE e pesticidas -HCH, - CH, HCB, oxy-chlordane e t-nonachlor tiveram níveis acima do LOD em mais de 70% das amostras. PCB 118 foi significativamente diferente nas áreas, com concentração maior na industrial (Campinas; 4.64). O organoclorado p-p’-DDE na zona rural de Ribeirão Preto; (123.05) foi maior que na urbana de Vila Nova Cachoeirinha. A mediana do ß-HCH para as áreas foi 6.31, significativamente maior na zona rural de Botucatu (18.20). A maior concentração de oxy-chlordane (3.59) e de t-nanochlor (1.17) foi na zona rural de Ribeirão Preto (p<0.05), diferentes também da área urbana (Leonor Mendes de Barros; p<0.05). CONCLUSAO: As concentrações das PTS foram baixas com diferenças entre as áreas; os maiores valores estavam nas parturientes da zona rural.

Persistent organic pollutants (POPs) present in the living environment are thought to have detrimental health effects on the population, with pregnant women and the developing foetus being at highest risk. We report on the levels of selected POPs in maternal blood of 160 delivering women residing in different regions within the São Paulo State, Brazil. Overall levels of measured compounds were found to be low with only PCBs 118, 138, 153 congeners, p-p’-DDE metabolite, -HCH, -HCH, HCB, oxy-chlordane and t-nonachlor pesticides having levels above LOD in more than 70% of the samples, thus comparisons between sites were performed for those compounds only. Statistical differences between sites were only observed for PCB 118 congener, with the highest concentration measured in the industrial site – Campinas (4.7 ng/g lipids). The p,p’-DDE metabolite was detected in all participants, with the median for all sites being 58.2 ng/g lipids, and large regional differences were evident. The highest levels of p,p’-DDE were measured in the rural 2 site – Ribeirão Preto with a median of 123 ng/g lipids that was significantly higher if compared with the urban 2 site (São Paulo City). The median concentration of ß-HCH for all sites was 6.31 ng/g lipids with the significantly highest concentration found in the rural 1 site – Botucatu (18.20 ng/g lipids). Oxy-chlordane was detected in all samples, with the highest concentration measured in the rural 2 site - Ribeirão Preto (3.6 ng/g lipids)¸which was found to be significantly higher than in all other sites The t-nonachlor compound was detected in 99% of samples with the highest concentration being 1.17 ng/g lipids, also in the rural 2 site- Ribeirão Preto. The level found in the rural 2 site was significantly higher than the level measured in the urban 3 site (São Paulo City)... (Complete abstract click electronic access below)
Keywords: Parto - Complicaçoes e sequelas; Pesticidas - Efeitos fisiológicos; Pesticides exposure; Human blood